The experiences of gratitude in female ulama: An interpretation from Sufi psychology and PERMA-Model perspective - Arikhah, Arikhah; Sessiani, Lucky Ade; Makmun, Muhammad; Safitri, Ririh Megah; Zuhri, Mishbah Khoiruddin (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Amidst the social-cultural predominance of male ulama in the religious context, female ulama play important roles and yet are often trapped in life-role complexity and gender bias, as they have a responsibility in both the domestic and public domains. This study aims to explore the meaning of the experience of gratitude among female ulama based on the perspective of positive psychology, with reference to the PERMA (Positive emotion, Engagement, Relationship, Meaning, and Accomplishment) model, with further interpretation of gratitude (shukr) from Sufi psychology. Using a qualitative (phenomenological) approach, we held online in-depth interviews with five female ulama participants from across Indonesia and Germany. The research demonstrates the interconnection between themes related to gratitude according to PERMA-Model and the embodiment of gratitude (shukr) in Sufi psychology. These findings provide evidence to support the practical implication of the integrative intervention of positive and Sufi psychology for clinical purposes or to promote flourishing and well-being among women.